If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3n + -6) = -3(5 + -7n) Reorder the terms: 4(-6 + 3n) = -3(5 + -7n) (-6 * 4 + 3n * 4) = -3(5 + -7n) (-24 + 12n) = -3(5 + -7n) -24 + 12n = (5 * -3 + -7n * -3) -24 + 12n = (-15 + 21n) Solving -24 + 12n = -15 + 21n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-21n' to each side of the equation. -24 + 12n + -21n = -15 + 21n + -21n Combine like terms: 12n + -21n = -9n -24 + -9n = -15 + 21n + -21n Combine like terms: 21n + -21n = 0 -24 + -9n = -15 + 0 -24 + -9n = -15 Add '24' to each side of the equation. -24 + 24 + -9n = -15 + 24 Combine like terms: -24 + 24 = 0 0 + -9n = -15 + 24 -9n = -15 + 24 Combine like terms: -15 + 24 = 9 -9n = 9 Divide each side by '-9'. n = -1 Simplifying n = -1
| 18p+3z-56=14-z | | 9.2x-8=2.2x+13 | | -5+5x= | | 9h^2-16=0 | | -(m-4)=-3(m-6) | | (3x+1)=(2x-8) | | C=(b+rm)(l+t) | | (x-2)*(x+5)=400 | | 5(3m+6)=57 | | -5(x+3)=7-(5+x) | | 12x-4=8x-37 | | 8/5x-3=16-2/5x | | P^2-14p+24=0 | | 3(v-2)-6v= | | 4(4-7n)=2(8-n) | | -6x+-5x= | | (46+2x)(65+2x)=4740 | | 3r^2-24r+45=0 | | 12p^2+8p+1=0 | | 3y^3+16y+5=0 | | 4(-b+7)=-(1+7v) | | (x-8)(x+7)=56 | | 17x+-12=114+3 | | 5g^2+44g-9=0 | | 5x+2(5x+8)=8x+18 | | 6p+-3(4p+3)+4(6p+1)=43 | | 5(m-2)=-(6m-1) | | x(x-9)(x+3)=0 | | Z-6.8=7.56 | | 0=6x+x^2-31 | | 1620x-350=680x+470 | | 1/3p-p=12 |